Computed tomography–related radiation exposure in children transferred to a Level I pediatric trauma center. Issue 6 (June 2015) - Brinkman, Adam S.; Gill, Kara G.; Leys, Charles M.; Gosain, Ankush
Abstract : PURPOSE: Pediatric trauma patients presenting to referring facilities (RF) often undergo computed tomography (CT) scans to identify injuries before transfer to a Level I pediatric trauma center (PTC). The purpose of our study was to evaluate RF compliance with the American College of Radiology (ACR) guidelines to minimize ionizing radiation exposure in pediatric trauma patients and to determine the frequency of additional or repeat CT imaging after transfer to a PTC. METHODS: After institutional review board approval, a retrospective review of all pediatric trauma admissions from January 2010 to December 2011 at our American College of Surgeons Level I PTC was performed. Patient demographics, means of arrival, Injury Severity Score, and disposition were analyzed. Patients who underwent CT were grouped by means of arrival: those who were transferred from an RF versus those who presented primarily to the PTC. Compliance with ACR guidelines and need for additional or repeat CT scans were assessed for both groups. RESULTS: Six hundred ninety-seven children (aged <18 years) were identified, with a mean age of 10.6 years. Three hundred twenty-one (46%) patients presented primarily to the PTC. Three hundred seventy-six (54%) were transferred from an RF, of which 90 (24%) patients underwent CT imaging before transfer. CT radiation dosing information was available for 79 (88%) of 90 patients. After transfer, 8 (9%) of 90 of children imaged at an RF required additional CT scans. In comparison, 314 (98%) of 321 patients who presented primarily to the PTC and underwent CT received appropriate pediatric radiation dosing. Mean radiation dose at PTC was approximately half of that at RF for CT scans of the head, chest, and abdomen/pelvis ( p < 0.01). CONCLUSION: Pediatric trauma patients transferred from RF often undergo CT scanning with higher than recommended radiation doses, potentially placing them at an increased carcinogenic risk. Fortunately, few RF patients required additional CT scans after PTC transfer. Finally, compliance with ACR radiation dose limit guidelines is better achieved at a PTC. LEVEL OF EVIDENCE: Care management study, level IV.